Oral Pyogenic Granuloma That Mimics Malignancy in Two Geriatric Patients - Selçuk, Ömer Tarık; Günsoy, Behçet; Ünlü, Ceren Ersöz (Fırat University, 2012)
Pyogenic granuloma is a benign vascular lesion which occurs secondary to trauma. It is frequently seen on mucosa and skin. It is mostly localized on gingiva, and occurs at second and third decades of life. 65 year-old male presenting with a sublingual mass growing for four months, and 87 year-old female presenting with a mass localized on left buccal mucosa were examined. Lesions were totally excised with surgical borders and reconstructed properly. Postoperative histopathologic results were reported as pyogenic granuloma. Pyogenic granulomas can look like malign lesions in geriatric patients. For this reason we report two cases of oral pyogenic granuloma in geriatric patients with oral with a review of current literature.

Piyojenik granülom, travmaya sekonder gelişen benign yapıda vasküler lezyondur. Mukoza ve ciltte sıklıkla görülür. Sıklıkla gingivada yerleşim gösterir ve yaşamın ikinci ve üçüncü dekatlarında görülmektedir. 65 yaşındaki erkek hastada, son 4 aydır büyüme gösteren sublingual kitle ve 87 yaşındaki bayan hastada sol bukkal mukozada vejetan kitle saptandı. Kitleler cerrahi sınırlarla birlikte total eksize ve uygun şekilde rekonstrükte edildi. Her iki hastada da postoperatif patoloji sonucu, piyojenik granülom olarak raporlandı. Oral kavite yerleşimli bu iki geriatrik piyojenik granülom olgusu; geriatrik hastalarda malign lezyonlarla karışabilmesi nedeni ile güncel literatür eşliğinde sunulmuştur.
Geriatrik İki Hastada Maligniteyi Taklit Eden Oral Piyojenik Granülom